Toward a Pedagogically Driven Framework for Designing a Socioscientific Inquiry-Based Learning (SSIBL) Digital Platform - Muhamad Yusup; Hamdi Akhsan; Murniati; Devi Ardiantini; Desilawati (Jurnal Penelitian Pendidikan IPA, 2026)
Socioscientific Inquiry-Based Learning (SSIBL) requires instructional continuity across contextual exploration, scientific inquiry, evidence construction, argumentation, and assessment. However, existing digital learning environments often support these activities in isolation, resulting in fragmented pedagogical processes. This study proposes a pedagogically driven framework for designing a Socioscientific Inquiry-Based Learning (SSIBL) digital platform through the systematic identification of instructional needs, synthesis of cross-phase instructional functions, derivation of system-level design requirements, and development of an architectural framework. A design-oriented requirement elicitation approach was employed involving 45 senior high school students and six physics teachers. Data were collected using structured questionnaires covering six phases of the SSIBL workflow and analyzed through descriptive analysis, cross-phase pattern identification, instructional function synthesis, requirement translation, and architectural framework development. The findings revealed consistently high instructional needs across all SSIBL phases and identified four cross-phase instructional functions: Epistemic Structuring, Evidence Construction, Deliberative Anchoring, and Orchestration Visibility. These functions informed the derivation of system-level design requirements and the development of an architectural framework that preserves instructional continuity throughout SSIBL. The study contributes a transparent pedagogically driven framework that bridges instructional theory and educational technology design, providing a conceptual foundation for future platform development and design-based research.